Self-stochasticity phenomenon in dynamical systems generated by difference equations with continuous argument - Romanenko, O. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
For dynamical systems generated by the difference equations x(t+1) = f(x(t)) with continuous time (f is a continuous mapping of an interval onto itself), we present a mathematical substantiation of the self-stochasticity phenomenon, according to which an attractor of a deterministic system contains random functions.